Electrodes influence on the characterization of the electrical properties of colossal permittivity CaCu3Ti4O12 ceramics. Issue 21 (1st November 2022) - Mao, Pu; Lu, Gang; Yan, Qingsong; Annadi, Anil; Guo, Yongguang; Wang, Zepeng; Liu, Zhiyong; Xie, Bing; Zhang, Lixue
Abstract: Electrode selection and its effects are extremely crucial to characterize the electrical properties and understand the colossal permittivity response of CaCu3 Ti4 O12 (CCTO) ceramics. However, the specifical correlation between metal electrode and electrical performances of CCTO ceramics are not clear so far. In this study, we have systematically investigated the effects of metal electrodes (Ag, Au and Pt) on the colossal permittivity response, dielectric loss, nonlinear characteristics and dielectric relaxation behavior of CCTO ceramics prepared via solid-state reaction means. Moreover, the related physical mechanisms of electrode effect on the electrical properties of CCTO ceramics have been analyzed. As a result, it is found that the metal electrode plays a minimal effect on the dielectric constant of CCTO ceramics in low and intermediate frequencies (10 2 –10 5  Hz), but the Pt-CCTO ceramic presents a reduced dielectric constant in a frequency range of 10 4 –10 5  Hz due to the relatively weaker grain boundary responses and the lower Schottky barriers between Pt electrode and sample surface. Meanwhile, the dielectric constant of Pt-CCTO ceramics sharply decreases at the high frequencies, which may be attributed to the greater dipole-dominated dielectric relaxation behaviors induced by the Pt electrode. Furthermore, the influence of electrode on dielectric loss is relatively significant, especially at the intermediate and high frequencies under high temperatures. Whereas, the influences of electrode effect on the breakdown electric field strength and nonlinear coefficient of CCTO ceramics are relatively little, as revealed by nonlinear characteristics. Consequently, it is comprehensively considered that the Ag electrode is more suitable to characterize the electrical performances of CCTO ceramics. Our results may provide a guidance to select electrodes and further understand the colossal dielectric mechanism for all the dielectric ceramics.